BROILER GENOTYPING AND ALLILIC FREQUNCY ANALYSIS BY PCR-RFLP FOR IGF1 AND IGF2 GENES - Al-Hassani, Ali S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate Broiler chickens using PCR-RFLP (IGF1 and IGF2 genes). HinfI and Hsp92II restriction enzymes were used to amplify and digest 793-bp and 1146-bp fragments of the IGF1 gene, respectively. TT, TC, and CC genotypes were found in both genes in two different T and C allele subgroups. IGF1 had a higher prevalence of the C-allele (0.86) than IGF2, whereas IGF2 had a higher prevalence of the T-allele (0.5611).